The effect of intraperitoneal instillation of drugs on postoperative analgesia after laparoscopic cholecystectomy: a network meta-analysis - Zhang, Dongmei; Wang, Xiaojiao; Yang, Xiaoli; Xia, Dajian (Frontiers in Pharmacology, 2025)
BackgroundPostoperative pain is a critical factor contributing to delayed discharge and postoperative recovery after laparoscopic cholecystectomy (LC). Intraperitoneal instillation of analgesic agents has been proposed as a means to alleviate pain in patients undergoing LC. This study aimed to evaluate the efficacy of various drugs administered via intraperitoneal instillation for postoperative analgesia after LC using a network meta-analysis approach.MethodsA comprehensive search was conducted in PubMed, EMbase, Web of Science and Cochrane Library databases from inception to August, 2025. Randomized controlled trials (RCTs) investigating the effects of intraperitoneal instillation on post-LC analgesia were included. Two independent reviewers screened studies, extracted data, and assessed the risk of bias. A frequentist network meta-analysis was performed to estimate standardized mean differences (SMDs) and 95% confidence intervals (CIs). The surface under the cumulative ranking curve (SUCRA) was used to rank the interventions for each outcome.ResultsEleven RCTs comprising 667 patients were included. According to SUCRA values, bicarbonate (96.5%) ranked highest in reducing VAS scores at 24 h post-surgery. Acetazolamide (85.9%) was most effective at 12 h, MgSO4 (98.4%) at 6 h, and ondansetron (96.4%) at 2 h. Dexamethasone was associated with the lowest analgesic consumption (SUCRA: 95.3%) and the longest time to first analgesic request (81.5%).ConclusionIntraperitoneal instillation of bicarbonate, acetazolamide, MgSO4, and ondansetron provides differential analgesic benefits at various time points after LC. Dexamethasone appears to be a promising adjunctive agent for reducing analgesic requirements and prolonging the duration of analgesia.